PENGUATAN BUDAYA LITERASI DI MASYARAKAT MELALUI PELATIHAN DAN PENDAMPINGAN LITERASI INFORMASI - NAIMAH, JAINATUN; Putri Roka Ismail; Hidayatul Munawwarah S; Isnaini; Sesilia Novitry Tafonao (LPPI UMN AL WASHLIYAH, 2025)
Abstract This community service program aims to enhance the literacy culture and information literacy skills of the community in Marindal II Village, Patumbak District, Deli Serdang Regency. The activity was initiated due to the community’s limited understanding of literacy, which was still confined to basic reading and writing abilities. Using the community education method, the program was carried out through socialization, training, and mentoring activities involving village officials, members of the Family Welfare Empowerment (PKK), and children at the Marindal II Youth Reading Park (TBM). The implementation took place over two days, from August 22 to 23, 2025. The first day focused on raising awareness of the importance of information literacy among village officials and families, while the second day emphasized interactive reading sessions, educational games, and short story writing competitions with children at the TBM. The results indicated an improvement in the community’s understanding of information literacy concepts, their ability to evaluate the credibility of information sources, and an increase in reading and writing interest among children. Moreover, the activity successfully fostered collaboration between local government, the TBM community, and residents in creating an environment that supports a sustainable literacy culture. Therefore, strengthening literacy culture through training and information literacy mentoring serves as an effective strategy to build an intelligent, critical, and competitive society in the digital era. Keywords: information literacy, literacy culture, community training, community reading park, empowerment